2005
DOI: 10.1227/01.neu.0000176877.26994.0c
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Magnetic Resonance Imaging-related Heating in Deep Brain Stimulation Leads Using a Lead Management Device

Abstract: Small, concentric loops placed around the burr hole seem to reduce MRI-related heating for these implants. Although the mechanism is still not fully understood, a device such as that used in the present study could permit a wider range of clinical scanning sequences to be used at 1.5 and 3 T in patients with DBS implants, in addition to increasing the margin of safety for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 11 publications
5
78
2
Order By: Relevance
“…In contrast to this and other recent studies, where a fluoroptic probe was used, the temperature changes were measured with an infrared camera. These low temperature changes are in contrast to the study of Baker et al [3], who found temperature changes up to 10°C in their setup. The major difference seems to be the length of the used DBS leads.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to this and other recent studies, where a fluoroptic probe was used, the temperature changes were measured with an infrared camera. These low temperature changes are in contrast to the study of Baker et al [3], who found temperature changes up to 10°C in their setup. The major difference seems to be the length of the used DBS leads.…”
Section: Discussioncontrasting
confidence: 99%
“…Several authors have investigated the effect of MRI on DBS [1,2,3,4,5,6,7,8] and spinal cord stimulation devices [7,9,10] using different field strengths, sequences and implanted devices. On the other hand, there are studies published where patients were examined without restricted protocols, exceeding the manufacturer's recommendations [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For a wholebody averaged SAR of 3.9 W/kg, the rise was 25.3 • C for no loops in the lead and 6.1 • C when the leads were positioned with two small loops (approximately 2.5 cm in diameter) in an axial orientation at the top of the head portion of the phantom, simulating a loop near the burr hole cover. Similarly, Baker et al found that the presence of loops in the lead resulted in decreased temperature rise [35]. Kainz et al [36] also undertook a study of heating of neurostimulation systems.…”
Section: Review Of Heating Of Leads By the Rf Field Used For Mrimentioning
confidence: 99%
“…(The phantom used in [34], [35], and [37] yields a temperature rise similar to that of the greatest gelling agent concentration considered by Park et al) Differences in phantom material may thus account for some of the differences in RF-induced heating reported in the peer-reviewed literature.…”
Section: Review Of Heating Of Leads By the Rf Field Used For Mrimentioning
confidence: 99%
“…Overall at 0.35T [103] and 1.5T it has been found that risks can be managed under specific configurations (low SAR sequences and often a head transmit-receive coil) and the production of heating is less when DBS equipment are fully implanted [34,59,[104][105][106][107][108][109][110][111][112][113]. In 3T MRI fields and higher [34,59,107,[109][110][111][114][115][116][117][118], similar results in terms of heating have been obtained but more caution is required when dealing with DBS implants and wires as well as pulse sequences in general require greater SAR. The summaries of the safety studies of DBS external electrodes and implants in MRI are listed in Table 2.…”
Section: Survey Of the Experimental Literature On The Safety Of Scalpmentioning
confidence: 99%